Stability Analysis of Catamaran Passenger Vessel with Solar Cell Energy in Calm Water - Dedi Budi Purwanto; Aries Sulisetyono; Teguh Putranto (IPTEK The Journal for Technology and Science, 2017)
The use of solar energy as the driving force for the ship's tour seems to be a major theme in efforts to create a marine transportation that are environmentally friendly as part of the Energy Efficiency Design Index (EEDI) for the reduction of pollutant levels. The electrical energy generated by solar energy is not as much energy from fossil fuels so that the solar panel powered ship that can only be engaging with a limited range and speed.This type of catamaran hull design that has two symmetrical hull which allows to have an expansive deck, small boat barriers and good stability. The shape of the deck of the ship will contribute extents solar panels that can be utilized as a producer of power required at the time of calculation of powering the vessel. The analysis of the stability of the vessel performed numerically with reference to the IMO regulations requiring minimum value stability arm at certain angles. The output of this research is catamaran vessel that have battery, solar panel, electric motor moving with speed 5 knots.